Students' Attitudes Towards South America: Results of an Empirical Study of the Seventh Grade - Grounds, Bettina (Journal of Geography Education, 2006)
Facing persistent stereotypes towards the continent of South America and its people in everyday teaching was the inspiration for repeating in 2002 two studies conducted by Kross in 1977 and 1989 about students' attitudes towards South America. In the study of 2002, students with "taught" knowledge and students with no "taught" knowledge were polled about their perceptions of South America. The results show that teaching about South America is able to improve students' knowledge about the continent and therefore to reduce negative stereotypical views of its countries and their inhabitants. Compared to the previous studies, the contemporary students' knowledge was deeper, but not as diffused among the students, as it was in 1977 and 1989. Another remarkable result was the change in the perception of the political situation in South America. In 1989 the tested students focussed on the unjust social situation between the classes. This aspect did not occur at all in 2002, which might reflect changes in the political landscape of the continent. The recent study in its comparison to former studies shows the ability of geographical teaching to reduce stereotypes and to help form objective attitudes to other continents and cultures.